Development of Digital Interface for Waterway Service Support Application in Amazonas (Estudos em Design, 2021)
More than one-third of the largest freshwater basin on the planet is located within the state of Amazonas. As the region is crossed by rivers, waterway transportation assumes a role not only of locomotion, but of supply, communication, and connection between the municipalities. Despite the great importance that river navigation has, there were few technological advances applied to facilitate the undertaking of activities within the sector. Considering this context, this article intends to elaborate a proposal of a mobile application interface for buying and selling regional boat tickets. To carry out this research, the Project E project method (MEURER and SZABLUK, 2010) was applied to understand the structure of the ticket sales service and to develop a digital interface with functions that would collaborate with the execution and modernization of the ticket sales service. The result was an easy-to-navigate graphical user interface rated as good and excellent by the users who tested it.
Keywords: Interface design; User experience; Tickets selling; Water transportation; Amazon boats